PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU (Survei pada Guru di SMA Negeri Se-Kabupaten Kuningan) - YATI MARYATI; AGIE HANGGARA (Universitas Kuningan, 2022)
AbstractThe low performance of teachers is the issue behind this research. A phenomenon that often occurs in the field, shows that there are still teachers who are not maximal in the learning and evaluation process, use of time at work inefficiently, lack of collaboration with other teachers and show low morale. By collecting the results of teacher administration at Senior high schools in Kuningan, researchers carried out a field study that shows that they are still not fully collecting administration. The low performance of the teacher is thought to be influenced by the principal's leadership factor as the head of the school, the school work environment, and the teachers' work motivation.This study aims to determine first the influence of principal leadership on work motivation in Senior high schools in Kuningan; second, the influence of work environment on work motivation in Senior high schools in Kuningan; third, the influence of principal leadership on the performance of teachers in Senior high schools in Kuningan; fourth, the influence of work environment on teacher performance in Senior high schools in Kuningan; fifth, the influence of work motivation on teacher performance in Senior high schools in Kuningan. The method used in this research is descriptive and correlational methods. while the sample used is 233 teachers in Senior high schools in Kuningan.The results showed that; 1) there is a positive influence of leadership on work motivation in Senior high schools in Kuningan; 2) there is a positive influence of work environment on work motivation in Senior high schools in Kuningan; 3) there is an influence of principal leadership on teacher performance in Senior high schools in Kuningan; 4) there is an influence of the work environment on the performance of teachers in Senior high schools in Kuningan; 5) there is an influence of work motivation on teacher performance in Senior high schools in Kuningan. Based on the research results, it can be concluded that the principal's leadership has a positive effect on work motivation; the work environment has a positive effect on work motivation; Principal leadership has a positive effect on teacher performance; The work environment has a positive effect on teacher performance; Work motivation has a positive effect on teacher performance in Senior high schools in Kuningan. Keywords: Principal Leadership, Work Environment, Work Motivation, Teacher Performance.AbstrakPermasalahan dalam penelitian ini adalah masih rendahnya kinerja guru. Fenomena yang terjadi menunjukan masih terdapat guru yang kurang maksimal dalam proses pembelajajaran dan evaluasi, penggunaan waktu dalam kerja, dan kejarsama dengan orang lain dalam bekerja yang kurang serta menunjukan semangat kerja yang rendah. Peneliti melakukan studi lapangan dengan mengumpulkan hasil adminitrasi guru pada SMA Negeri di Kabupeten kuningan yang menunjukan masih belum sepenuhnya dalam mengumpulkan adminitrasi. Rendahnya kinerja guru diduga dipengaruhi oleh faktor kepemimpinan kepala sekolah sebagai pemimpin kepala sekolah, lingkungan kerja yang ada di sekolah serta motivasi kerja yang dimiliki oleh para guru. Penelitian ini bertujuan untuk mengetahui pengaruh kepemimpinan kepala sekolah terhadap motivasi kerja di SMA Negeri Se-Kabupaten Kuningan; Untuk mengetahui pengaruh lingkungan kerja terhadap motivasi kerja di SMA Negeri Se-Kabupaten Kuningan; Untuk mengetahui kepemimpinan kepala sekolah terhadap kinerja guru di SMA Negeri Se-Kabupaten Kuningan; Untuk mengetahui lingkungan kerja terhadap kinerja guru di SMA Negeri Se-Kabupaten Kuningan; Untuk mengetahui motivasi kerja terhadap kinerja guru di SMA Negeri Se-Kabupaten Kuningan. Metode yang digunakan dalam penelitian ini adalah deskriptif dan metode korelasional. Dan sampel yang digunakan adalah 233 guru di SMA Negeri Se-Kabupaten Kuningan. Hasil penelitian menunjukan bahwa; kepemimpinan kepala sekolah berpengaruh positif terhadap motivasi kerja di SMA Negeri Se-Kabupaten Kuningan; lingkungan kerja berpengaruh positif terhadap motivasi kerja di SMA Negeri Se-Kabupaten Kuningan; Kepemimpinan kepala sekolah berpengaruh positif terhadap kinerja guru di SMA Negeri Se-Kabupaten Kuningan; Lingkungan kerja berpengaruh positif terhadap kinerja guru di SMA Negeri Se-Kabupaten Kuningan; Motivasi kerja berpengaruh positif terhadap kinerja guru di SMA Negeri Se-Kabupaten Kuningan.Kata Kunci : Kepemimpinan Kepala Sekolah; Lingkungan kerja; Motivasi kerja; Kinerja guru